Fast-track microwave-assisted synthesis of CdMoO4 and CdWO4 nanoparticles for hybrid rGO/NPs electrodes in high-performance supercapacitors - Vivas, Leonardo; Manquian, Carolina; Pacheco-Catalán, Daniella Esperanza; Márquez, Paulina; Singh, Dinesh Pratap (Frontiers in Energy Research, 2025)
Fast and facile synthesis of nanomaterials is always a challenge for industrial applications in various sectors. In this work, CdMoO₄ and CdWO₄ nanoparticles are synthesized by using a fast and cost-effective microwave-assisted method. The synthesized nanoparticles are mixed with reduced graphene oxide (rGO), to form active electrode materials for supercapacitor and their electrochemical performances were studied in detail. The electrodes were prepared by simple mixtures of rGO/CdMoO₄ and rGO/CdWO₄, and electrochemical performance were measured in both, two- and three-electrode configurations. In general, both rGO/CdMoO₄ and rGO/CdWO₄ mixtures exhibit an increased specific capacitance (Cp) compared to pure rGO. Notably, the rGO/CdMoO₄ mixture shows a Cp exceeding 543 Fg⁻1 at a scan rate of 5 mVs⁻1, which represents a significant improvement over rGO alone (Cp = 225 Fg⁻1). This increase in Cp can be attributed to the higher surface area of the rGO/CdMoO₄ electrode material due to smaller size of CdMoO₄ nanoparticles and their intercalation between the rGO layers in comparison to the rGO/CdWO₄ electrode material. Furthermore, the rGO/CdMoO₄ mixture demonstrated 77% capacitance retention over 5,000 charge/discharge cycles in the two-electrode configuration. The promising electrochemical performance and rapid, low-cost synthesis suggest that these materials have great potential for further use in high efficiency energy-storage devices.